Unveiling the effect of three- dimensional bioactive fibre mesh scaffolds functionalized with silanol groups on bacteria growth - Rodrigues, A. I. (2016)
There is an increasing clinical need to design novel biomaterials that combine bone regenerative potential with antibacterial properties. Silicon-based biomaterials, widely studied for application in bone regeneration, have demonstrated antibacterial properties. Herein, the aim of this work was to investigate the potential of the functionalization of biomaterials surfaces with silanol groups to prevent the bacterial biofilm formation. For that, we evaluated the adherence and biofilm formation of Escherichia coli (Gram negative) and Staphylococcus aureus (Gram positive) in SPCLbased scaffolds. We functionalized three-dimensional fibre meshes scaffolds with silanol (Siâ OH) groups by wet-spinning using a calcium silicate solution as a nonsolvent. The functionalization of the scaffolds was confirmed by X-ray photoelectron spectroscopy. The adherence of E. coli and S. aureus to the scaffolds was then investigated. After a growth period of 12h, the SPCL scaffolds functionalized with Si- OH groups showed lower bacterial adherence of E. coli and S. aureus. Biofilm formation was not visible in both scaffolds. The functionalized scaffolds showed an effect in preventing the formation of biofilm of S. aureus however, the same results were not found for E. coli, suggesting that silanol groups may only have a positive effect preventing the proliferation of gram-positive bacteria. The in vitro biological assessment of the functionalized materials showed these materials sustained cell proliferation and induced their osteogenic differentiation. The results suggest that the presence of Si-OH groups in SPCL scaffolds maintained bactericidal activity against S. aureus. Further research is still needed in order to understand the full antibacterial potential of silanol groups.